2020
DOI: 10.2503/hortj.utd-101
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Temperature and Timing/Duration of Night Cooling Treatments on Flowering Time and Quality of Cut Flowers of Standard Type Carnation (<i>Dianthus caryophyllus</i>)

Abstract: The aim of this study was to develop efficient night cooling technology to produce high-quality carnation cut flowers. The effects of temperature and timing of night cooling treatments (applied using a heat pump) on the flowering time and quality of cut flowers were investigated for standard type carnation flowers grown in a greenhouse in hot conditions. In the first experiment, rooted cuttings of the carnation 'Exceria' were planted in a greenhouse on July 6, 2012. Night cooling treatments at 18°C, 21°C, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 15 publications
3
4
0
Order By: Relevance
“…Further-more, the developmental stages of flower buds at the same node positions proceeded through three stages under EOD-cooling conditions compared with under either non-cooling or EON-cooling conditions. Thus, EOD-cooling in glass greenhouses promotes both bud initiation and flower development, which may increase flower blooming as previously reported (Higashiura et al, 2020). Dahab (1967) reported that the lower the night temperature, the lower the node position of flowering in 'William Sim' carnation.…”
Section: Discussionsupporting
confidence: 63%
See 4 more Smart Citations
“…Further-more, the developmental stages of flower buds at the same node positions proceeded through three stages under EOD-cooling conditions compared with under either non-cooling or EON-cooling conditions. Thus, EOD-cooling in glass greenhouses promotes both bud initiation and flower development, which may increase flower blooming as previously reported (Higashiura et al, 2020). Dahab (1967) reported that the lower the night temperature, the lower the node position of flowering in 'William Sim' carnation.…”
Section: Discussionsupporting
confidence: 63%
“…We reported previously that an EOD-cooling treatment reduces both the days to flowering and the number of nodes at flowering compared with the control (non-cooling) in carnation (Higashiura et al, 2020). This may result from the promotion of flower differentiation by short-term cooling.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations